HUBUNGAN MORFOLOGI DAN KEKUATAN OTOT QUADRICEPS FEMORIS DENGAN PATELLO FEMORAL PAIN SYNDROME DAN PERFORMA FUNGSIONAL PADA ATLET LEVEL 1 - Ni Putu Diah Asyana Putri; Adhitya, I Putu Gde Surya; Dewi, Anak Ayu Nyoman Trisna Narta (Kinetic and Physiotherapy Comprehensive, 2024)
Background: Patellofemoral pain syndrome (PFPS) is a clinical condition characterized by anterior knee pain common in athletes. Many factors cause (PFPS), one of which is the weakness of the quadriceps femoris (QF) muscle. Weakness of the QF muscle causes the knee to be unstable, which may affect an athlete's functional performance. The purpose of this literature review was to determine the relationship of QF muscle morphology and strength to PFPS and functional performance in level 1 athletes.  Methods: This study used a literature review method. Articles were searched through PubMed and Google Scholar using the keywords "Quadriceps Femoris Morphology," "Quadriceps Muscle Strength," "Patello Femoral Pain Syndrome," "Anterior Knee Pain," and "Functional Performance." The inclusion criteria were literature published by credible institutions and related to patellofemoral pain syndrome and functional performance. The exclusion criteria were a literature that did not use ultrasound and single-leg hop test measurement tools and published more than ten years ago. Results: From the five literature reviewed, there was a relationship between the morphology and strength of the Quadriceps Femoris muscle with Patello Femoral Pain Syndrome due to the thickness of the Quadriceps Femoris tendon and patella due to QF muscle tension and a decrease in QF muscle strength in PFPS patients. There is a relationship between the morphology and strength of the QF muscle and functional performance due to the thickness and strength of the QF muscle, which is associated with functional performance components, one of which is jumping ability.  Conclusion: This study suggested that there might be an association between QF muscle morphology and strength and PFPS, and there might be an association between QF muscle morphology and strength and functional performance. Thus, future research was needed to explore the correlation of these variables.